RELATIONS OF SEVERAL PHYSICOCHEMICAL PARAMETERS AND PHYTOPLANKTON IN COASTAL KUBU RAYA DISTRICT, WEST KALIMANTAN - Sri Endah Purnamaningtyas; Dimas Angga Hedianto; . Riswanto (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
This research was conducted in April, July and October 2013 at 8 (eight) stations: 1. Tj. Intan, 2. Tj. Tempurung, 3. Tj. Bunga Dalam, 4. Tj. Bunga dalam, 5. Tj. Burung, 6. P. Dabung, 7. Tasik Malaya, and 8. Tj. Harapan. This study aims to determine the relationship between several physic-chemical parameters and phytoplankton abundance. The results show the growth of phytoplankton biomass (chlorophyll a) was determined by high concentration of NH4 and NO3, while its growth is limited by turbidity (turbidity). Station that has high fertility in the Coastal District of Kubu Raya is Dabung Island. Keyword: water quality, chlorophyll a, coastal Kubu Raya district